Sosialisasi Akses Pembiayaan UMKM Pada Lembaga Keuangan Syariah Di Kecamatan Muara Badak Kabupaten Kutai Kartanegara - Swadia Gandhi Mahardika; Muh Shadiqul Fajri AF; Akbar Lufi Zulfikar (CV. Multi Kreasi Media, 2023)
Capital is an obstacle faced by MSMEs. Sharia financing through various Islamic financial institutions is a solution to overcome these problems and, in general, encourage the growth of MSMEs. The purpose of this community service activity is to provide knowledge and understanding to MSMEs about the process of Islamic finance in various Islamic financial institutions. This service activity is carried out by disseminating access to financing capital to Islamic financial institutions by providing information on various executed contracts. Activities in the form of socialization followed by discussion and question and answer. Through this activity, MSME actors will better understand multiple Sharia regulations in business cooperation transactions, especially financing-related ones. In addition, participants also understand the versatility of the contracts implemented in the Sharia financing process offered by various Islamic financial institutions. The result of this activity is to recommend MSME actors be able to support ease of access for MSME actors in terms of applying for financing to Islamic financial institutions to be able to improve the wheels of the economy among MSMEs while continuing to implement Islamic business values ​​and principles.